Learning difficulties involving volumes of solids of revolution : a comparative study of engineering students at two colleges of Further Education and Training in South Africa - Engelbrecht, Johann C. (Johannes Cornelis), 1946- (University of Pretoria, 2013)
Thesis (PhD)--University of Pretoria, 2012.